Differentiate x^2 + xy + y^2 =1 implicitly.

Each part can be done separately, so x^2 becomes 2x, xy becomes dy/dx + y by product rule, y^2 becomes 2y(dy/dx) by chain rule, and 1 becomes 0. Hence the answer is 2x + y + (2y+1)dy/dx = 0, but the answer is commonly given in the form dy/dx = -(2x+y)/(2y+1)

Answered by Tutor80806 D. Maths tutor

3989 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Differentiate x^5 + 3x^2 - 17 with respect to x


Find the area under the curve y = (4x^3) + (9x^2) - 2x + 7 between x=0 and x=2


How do you integrate 3x^2 - 6x + 5 (wrt x)?


How would we evaluate (1/3)^-3/2 ?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences